Efeitos da exposição à nanopartícula de dióxido de titânio em hepatócitos de peixe zebra (Danio rerio, Hamilton, 1822). uma abordagem in vitro - Siqueira, Priscila Rodrigues de (2016)
Titanium dioxide nanoparticles (TiO2-NP) are commonly used in many industrial activities. Consequently, the daily consumption by humans is estimated in 5.4 mg day, with an input in the environment of 4.2 mg day per person, receiving or not appropriated treatment before disposure. The cytotoxicity, genotoxicity and mutagenicity of TiO2-NP were investigated using the established fish cell line derived from zebrafish (Danio rerio) liver (i. e. ZF-L cells). Prior to the evaluation of nanoparticle’s toxic potential, a careful characterization was realized in culture medium in the presence or not of fetal bovine serum (FBS). Regarding to the characterization in terms of size was accessed using a transmission electron microscope (TEM), the agglomeration potential and surface charge were accessed by diameter light scattering (DLS) and zeta potential measurements, respectively, using a spectrophotometer. TiO2-NP in environmentally relevant concentrations were tested for cytotoxicity, genotoxicity and mutagenicity. Cell viability was accessed by four different tests, the trypan blue assay (membrane integrity), MTT reduction assay (mitochondria), neutral red retention assay (lysosomes) and finally, induction of apoptosis and necrosis. Genotoxicity was determined by observing the fragmentation of DNA by the comet assay, while mutagenicity was determined by Cytokinesis-block micronucleus technique. The characterization showed that the FBS was effective in dispersing the nanoparticles and prevent the formation of large agglomerates allowing robust responses on the real toxicity of NP. After 24 hours of treatment, there was cell membranes rupture, decreasing cell viability to 35.33%, at the highest concentration (1.0 μg mL-1). Mitochondrial metabolic activity remained unchanged, but it was possible to detect the proliferation of lysosomes, which was mainly attributed to the NP endocytosis. The induction of apoptosis was 50.4%, and necrosis was 13.9%, both in the concentration 1.0 μg mL-1 TiO2-NP. In the case of necrosis, a result 10 times greater than that presented by the negative control. Added necrosis and apoptosis indicated a decrease in cell viability to 35.7%. The comet test showed the fragmentation of the DNA, it was also possible to observe the formation of micronuclei, bridges and shoots demonstrated by the micronucleus assay. In general, this study demonstrated that TiO2-NP, after 24 hours of exposure, significantly affect cell viability and cause DNA damage, which may become irreversible. In conclusion, this study showed the cytotoxic, genotoxic and mutagenic potential of TiO2-NP for ZF-L cells. Mitochondrial and lysosome responses require further studies on the effect of TiO2-NP on these organelles.